Juxtaposing Fiduciary Constitutionalism and Administrative Constitutionalism in the Context of Enhancing the Indonesian Constitution - Tan, David (Brawijaya Law Journal : Journal of Legal Studies, 2021)
A lot of literature discusses the role of state administration, but there is still very little that emphasizes the unique picture related to juxtaposing aspects of fiduciary constitutionalism with administrative constitutionalism, especially at the stage of constitutional legal studies with the context of constitutionalism in Indonesia. Implementing a fiduciary state administration is very much needed, but the most significant obstacle is the enigma of administrative constitutionalism. The purpose of this inquiry is to analyze the development of the Indonesian Constitution in the future by elaborating the theory of fiduciary constitutionalism, issues related to administrative constitutionalism, and discussions related to the incorporation of the former and the latter into the practice of legal and political representation in the Indonesian Constitution using the perspective of judicial engagement theory. The research method used is the doctrinal legal approach using secondary data in the legal literature to gain academic insight. This research finally leads to a conclusion that focuses on the aspects of fiduciary and administrative constitutionalism, which can explain this phenomenon in enhancing the Constitution in Indonesia through several internalized recommendations.